Studi Sistem Drainase Jalan Beliang Kota Palangka Raya - Novrianti, Novrianti (Media Ilmiah Teknik Sipil, 2017)
At this time the drainage conditions are channeled to the primary channel that leads to the river, using land use, making the recharge less and less. By paying attention to the floods in 2015 and several years, to find out, the research conducted on the Jalan Beliang Drainage Study System in Palangka Raya City. This study aims to find out the existing drainage systems and channels and knowing between rational debit (Qr) and channel debit (Qs) in the study area. Based on field data, the base width (b) varies between 0.16 m - 0.75 m, and the depth is between 0.35 m - 0.75 m. Results from the garuda XA area indicate that Qr <Qs per period 2, 5, 10, 25 cm is not flooded and is sufficient for dimensional capacity. The flood conditions that occurred during 2015 were a momentary inundation in certain locations in some places without channels. From the results of the study in several locations, there is no drainage and poor drainage is available, it is necessary to drain the drainage in the study area can flow air and not cause puddles. The need to redesign the flow discharge and flow direction so that it can flow properly. Research carried out in the region is always too high, because it experiences flooding in the primary canal and surrounding roads.